From penumbra. Prolegomena to poetic thought - Martín, Francisco José (Tropelías: Review of Literary Theory and Comparative Literature, 1995)
Starting from the platonic myth of the cavern, this paper intends to throw light on the difficult and tense relationship between philosophy and literature -a separation which has marked deeply the foundations of western culture. The continual references to myth serve to the purpose of hypothising the origins of that split. A new track is thus lit up, on which philosophy can be led to meet philosophy itself: the philosophy of thinking calling to poetry.